2016
DOI: 10.3892/ol.2016.4703
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency ultrasound-mediated microvessel disruption combined with docetaxel to treat prostate carcinoma xenografts in nude mice: A novel type of chemoembolization

Abstract: Abstract. The aim of the present study was to investigate whether low-frequency ultrasound (US)-mediated microvessel disruption combined with docetaxel (DTX) can be used as a novel type of chemoembolization. Mice were assigned to four groups: i) The USMB group, treated with low-frequency US combined with microbubbles (USMB); ii) the DTX group, treated with DTX; iii) the USMB + DTX group, treated with combined therapy; and iv) the control group, which was untreated. Immediately after the first treatment, the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Treatment with USMB alone was excluded from the present study for three reasons. Firstly, USMB alone can inhibit tumor growth, however, tumor growth occurs at a slower rate (18,19), which was further confirmed in our previous studies (20), therefore the combination of USMB with other therapies is suggested to treat cancer, rather than alone. Secondly, RFA is able to achieve complete ablation of tumors measuring <3 cm in diameter, however, eradication of larger tumors and avoiding proliferation of residual tumor cells remains a challenge.…”
Section: Cell Lines and Xenograft Tumor Model The Present Study Was supporting
confidence: 69%
“…Treatment with USMB alone was excluded from the present study for three reasons. Firstly, USMB alone can inhibit tumor growth, however, tumor growth occurs at a slower rate (18,19), which was further confirmed in our previous studies (20), therefore the combination of USMB with other therapies is suggested to treat cancer, rather than alone. Secondly, RFA is able to achieve complete ablation of tumors measuring <3 cm in diameter, however, eradication of larger tumors and avoiding proliferation of residual tumor cells remains a challenge.…”
Section: Cell Lines and Xenograft Tumor Model The Present Study Was supporting
confidence: 69%
“…The development of safe and effective antitumor therapies remains a major research hotspot. The use of ultrasound combined with microbubbles (USMB) has recently emerged as a promising method for destroying the tumor vasculature because of its ability to cause complete and persistent cessation of blood flow to the tumor ( Wood and Sehgal, 2015 ; Yang et al., 2016 ), which is mainly considered to occur through vascular dilation ( Wood et al., 2007 ; Wood et al., 2008 ; Levenback et al., 2012 ), thrombosis ( Huang et al., 2013 ; Foiret et al., 2017 ), and ultimate disruption of blood perfusion to the tumor ( Liu et al., 2012 ; Zhang et al., 2018 ). Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study by Kang et al (35) reported that DLLD combined with UTMD could effectively inhibit the growth of VX2 rabbit liver tumors by deferring proliferation and promoting apoptosis. Studies investigating the effect of DLLD combined with UTMD on the growth of other tumors, such as H22 HCC or MHCC-H hepatocellular carcinoma xenografts and prostate carcinoma xenografts, have also demonstrated that DLLD combined with UTMD was the most effective strategy for the inhibition of tumor cell proliferation and the promotion of apoptosis (28,38,39). Consistent with the aforementioned results, the results of the present study indicated that DLLD combined with UTMD could significantly inhibit DNA synthesis, promote cell accumulation in the G 2 /M phase and stimulate cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%